Socioeconomic inequality of unintended pregnancy in the Iranian population: a decomposition approach - Reza Omani-Samani; Mostafa Amini Rarani; Mahdi Sepidarkish; Esmaeil Khedmati Morasae; Saman Maroufizadeh; Amir Almasi-Hashiani (BMC, 2018)
Abstract Background There are several studies regarding the predictors or risk factors of unintended pregnancy, but only a small number of studies have been carried out concerning the socio-economic factors influencing the unintended pregnancy rate. This study aimed to determine the socioeconomic inequality of unintended pregnancy in Tehran, Iran, as a developing country. Methods In this hospital based cross-sectional study, 5152 deliveries from 103 hospitals in Tehran (the capital of Iran) were included in the analysis in July 2015. Socioeconomic status (SES) was measured through an asset-based method and principal component analysis was carried out to calculate the household SES. The concentration index and curve was used to measure SES inequality in unintended pregnancy, and then decomposed into its determinants. The data was analyzed by statistical Stata software. Results The Wagstaff normalized concentration index of unintended pregnancy (− 0.108 (95% Confidence Interval (CI) = − 0.119 ~ − 0.054)) endorses that unintended pregnancy is more concentrated among poorer mothers. The results showed that SES accounted for 27% of unintended pregnancy inequality, followed by the mother's nationality (19%), father's age (16%), mother's age (10%), father's education level (7%) and Body Mass Index (BMI) groups (5%). Conclusion Unintended pregnancy is unequally distributed among Iranian women and is more concentrated among poor women. Economic status had the most positive contribution, explaining 27% of inequality in unintended pregnancy.